Distinctive Regulation of Emotional Behaviors and Fear-Related Gene Expression Responses in Two Extended Amygdala Subnuclei With Similar Molecular Profiles - Ueda, Shuhei; Hosokawa, Masahito; Arikawa, Koji; Takahashi, Kiyofumi; Fujiwara, Mao; Kakita, Manami; Fukada, Taro; Koyama, Hiroaki; Horigane, Shin-ichiro; Itoi, Keiichi; Kakeyama, Masaki; Matsunaga, Hiroko; et al. (Frontiers in Molecular Neuroscience, 2021)
The central nucleus of the amygdala (CeA) and the lateral division of the bed nucleus of the stria terminalis (BNST) are the two major nuclei of the central extended amygdala that plays essential roles in threat processing, responsible for emotional states such as fear and anxiety. While some studies suggested functional differences between these nuclei, others showed anatomical and neurochemical similarities. Despite their complex subnuclear organization, subnuclei-specific functional impact on behavior and their underlying molecular profiles remain obscure. We here constitutively inhibited neurotransmission of protein kinase C-δ-positive (PKCδ+) neurons—a major cell type of the lateral subdivision of the CeA (CeL) and the oval nucleus of the BNST (BNSTov)—and found striking subnuclei-specific effects on fear- and anxiety-related behaviors, respectively. To obtain molecular clues for this dissociation, we conducted RNA sequencing in subnuclei-targeted micropunch samples. The CeL and the BNSTov displayed similar gene expression profiles at the basal level; however, both displayed differential gene expression when animals were exposed to fear-related stimuli, with a more robust expression change in the CeL. These findings provide novel insights into the molecular makeup and differential engagement of distinct subnuclei of the extended amygdala, critical for regulation of threat processing.